Ethical and legal issues in telemedicine : prospects and challenges - Abdul, Tijani Fatai (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2010)
The advancement in technology plays a major role in the development of medical profession. Benefits of telemedicine include quick delivery of healthcare services to the people in rural communities, as well as the exchange of healthcare information services across different geographical locations in the world. It reduces healthcare costs, improves the dissemination of information and training for healthcare providers and patients. However, the encroachment of technology into medical practice creates a range of new opportunities and challenges for policy makers, lawyers, patients, healthcare providers and other stakeholders in the healthcare industry. Therefore, the drawbacks from the advent of this new technology cannot be overlooked. Further, the ethical and legal issues such as physician-patient relationship, patient informed consent, privacy, confidentiality and security, issues of licensing, duty of care, standard of care and conflict of laws affecting the development of telemedicine must be considered. This thesis analyses some of the advantages and disadvantages of telemedicine, as well as ethical and legal issues affecting telemedicine and recommends solutions to the problems. Also, the research analyses the views of the Islamic medical ethics that must be observed by healthcare providers for the benefit of Ummah.